Increase in preterm births in Brazil: review of population-based studies - Silveira, Mariângela F; Santos, Iná S; Barros, Aluísio J D; Matijasevich, Alicia; Barros, Fernando C; Victora, Cesar G (Revista de Saúde Pública, 2008)
OBJECTIVE: The greatest cause of infant mortality in Brazil is perinatal conditions, mostly associated with preterm delivery. The objective of the study was to evaluate the evolution of preterm delivery rates in Brazil. METHODS: A review was conducted using the Medline and Lilacs databases, including published studies in periodicals, thesis and dissertations since 1950. Exclusion criteria were: studies related to clinical trials and those with complications at gestation and preterm delivery and care. Inclusion criteria were: population-based studies on prevalence of preterm delivery in Brazil, with representative sample of the studied population, and using primary data. Out of 71 studies found, analysis was carried out on 12. RESULTS: The prevalence of preterm delivery found ranged from 3.4% to 15.0% in the Southern and Southeastern regions between 1978 and 2004, with a rising trend from the 1990s onwards. Studies in the Northeastern region between 1984 and 1998 found prevalences of preterm delivery ranging from 3.8% to 10.2%, also with a rising trend. CONCLUSIONS: Data from the national live birth information system do not corroborate these trends. Rather, they show differences between the preterm rates given by this system and the rates measured in the studies included in this review. Because of the important role of preterm birth in relation to infant mortality in Brazil, it is important to identify the cause of these increases and to plan interventions that can diminish their occurrence.